Kata Penyukat dalam Bahasa Lasalimu - Yohanis Sanjoko (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
This study examines the classifier word in Lasalimu language. Classifier word a word that located behind numeralized and together with the word formed a phrase that called numbers phrase, which possible located in front of the nominal word. The purpose of this study was to describe the form and classification of classifier word in language of Lasalimu. This study used descriptive method with three stages, namely the stage of providing data, data analysis stage, and the stage of presenting the result of data analysis. Data analysis conducted after the data netted classified. The analysis is applied using apportion methods. The results of this study is form and classification in classifier word of Lasalimu language, namely (1) the classifier word for animals, (2) the classifier word for objects, and (3) the classifier word to humans. Each further divided into common classifier words and special classifier word.